2013
DOI: 10.1007/978-3-642-22508-6
|View full text |Cite
|
Sign up to set email alerts
|

Gold and Gold Mining in Ancient Egypt and Nubia

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a speci fi c statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…Harraz 2000;Klemm et al 2001;Zoheir et al 2008;Zoheir 2011;Klemm and Klemm 2013;Zoheir and Moritz 2014; and many others). However, thus far, no robust radiometric ages on the gold-bearing hydrothermal system have been obtained.…”
Section: The Fawakhir-el Sid Mining Districtmentioning
confidence: 95%
See 3 more Smart Citations
“…Harraz 2000;Klemm et al 2001;Zoheir et al 2008;Zoheir 2011;Klemm and Klemm 2013;Zoheir and Moritz 2014; and many others). However, thus far, no robust radiometric ages on the gold-bearing hydrothermal system have been obtained.…”
Section: The Fawakhir-el Sid Mining Districtmentioning
confidence: 95%
“…Langwieder (1994) concluded that the mineralized quartz veins are related to an open fissure system almost perpendicular to the NNW-shear direction through post-tectonic extension. Klemm and Klemm (2013) suggested that the elevated background gold concentrations (≤180 ppb Au) in fresh ophiolite and Hammamat molasse sediments from the Fawakhir area might indicate fertile source material for Au mineralization. Field observations led Klemm and Klemm (2013) to suggest a preliminary gold metallogenic model in the central Eastern Desert of Egypt, in which goldbearing quartz veins occur predominantly in ophiolite or in the Hammamat molasse sediments within an~500 m perimeter of granitic intrusions.…”
Section: Gold Mineralizationmentioning
confidence: 97%
See 2 more Smart Citations
“…Sabemos que se añadía sal y plomo para eliminar los residuos de plata al formarse cloruro argéntico que, junto con el plomo, constituía las escorias. Al cabo de cinco días el crisol se sacaba del fuego y el oro fundido se vertía en pequeñas vasijas en las que se enfriaba y solidificaba (Klemm, 2013).…”
Section: A Modo De Introducción: Un Viaje Desde La Prehistoria Hasta unclassified